The Ethics of Intellectual Property Rights in an Era of Globalization. Issue 4 (December 2013) - Shah, Aakash Kaushik; Warsh, Jonathan; Kesselheim, Aaron S.
<x xml:space="preserve">Abstract</x> Since the 1980s, developed countries, led by the United States and the countries of the European Union, have sought to incorporate intellectual property rights provisions into global trade agreements. These countries successfully negotiated the World Trade Organization's 1994 Agreement on Trade‐Related Aspects of Intellectual Property Rights (TRIPS), which required developing countries to adopt intellectual property provisions comparable to developed countries. In this manuscript, we review the policy controversy surrounding TRIPS and examine the two main ethical arguments articulated in its support — a theory of natural rights and a utilitarian argument. We contend that these theories provide insufficient bases for an intellectual property rights regime that compromises access to essential medicines in the developing world. While the policy community has engaged in active debate around the policy effects of TRIPS, scholars have not thoroughly considered the full ethical underpinnings of those policy arguments. We believe that a more robust understanding of the ethical implications of the agreement should inform policy discussions in the future.